Kesadaran dan Perlindungan Hukum bagi Pelaku UMKM di Kota Tegal - Muamar Riza Pahlevi; Faizal Yudhi Nugroho; Fajar Sigit Kusumajaya; Labib Fahmi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
This community service activity aims to provide an understanding of legal awareness and protection as a fundamental concept in the development of modern businesses for Micro, Small, and Medium Enterprises (MSMEs) in Tegal City. The program is focused on MSME actors who need knowledge about the importance of legal awareness and protection to enhance and develop their businesses. The methods used in this activity include initial observation, preparation of training materials, implementation of training, and evaluation. The results of the activity show an improvement in participants' understanding of the importance of legal awareness and protection in the context of modern business. The legal awareness held by MSME actors plays a crucial role in the development of more professional businesses and in avoiding legal issues. The participatory approach applied in this activity has proven to be effective in increasing legal awareness among MSME actors, as well as providing insights into the legal protection available to them amidst rapid modernization and global competition. This program is expected to contribute positively to the empowerment of MSME actors through a better understanding of the law.